Suppression of pseudogene MT2P1 transcription induced by E2F7 inhibits hepatocellular carcinoma cell proliferation and facilitates apoptosis via preserving its parental gene - Yiquan Lu; Yifan Zhang; Fengjie Hao; Nan Wang; Yongjun Chen; Junqing Wang (Cancer Biology & Therapy)
The majority of the pseudogenes are inert in normal transcription. Their transcripts are mostly attributed to non-coding RNAs that play various functions in human tumorigenicity and progression. Distinctively, pseudogene MT2P1 is universally transcribed in hepatocytes and presents a significant decrease in hepatocellular carcinoma (HCC). The effect of MT2P1-RNA on HCC cell proliferation and apoptosis needs investigation. MT2P1-RNA was detected by RT-qPCR assay in HCC tissues and cell lines, combined with the exploration of the public databases. The immunohistochemistry assay was used for testing the expression profile of E2F7 and the parental gene MT2A. The clinicopathological features of the patients were collected and analyzed. Ectopic expression of MT2P1-RNA in HCC cell lines was conducted, and the CCK8 assay and flow cytometry assay were carried out. Chromatin immunoprecipitation assay and Dual-luciferase reporter assay were, respectively, applied to validate the interaction between MT2P1, E2F7, and microRNA-15b-5p. The downregulation of MT2P1-RNA in HCC is negatively correlated with dismal clinicopathological features. MT2P1-RNA significantly suppressed HCC cell proliferation and induced apoptosis. E2F7 depletion sequentially elevated the level of MT2P1-RNA and MT2A, and E2F7 was validated as a suppressive transcription factor of the MT2P1 gene. The direct interactions of either MT2P1/miR-15b-5p or miR-15b-5p/MT2A were, respectively, ascertained, enlightening the ceRNA effect of them. The pseudogene-derived MT2P1-RNA is a suppressor of HCC by exerting the ceRNA effect on preserving MT2A, and its transcription is regulated by the suppressive transcription factor E2F7.